Theoretical exploration on free radical scavenging mechanism of curcumin analogues in water solvent - L S P Boli,, .- (IOP Publishing, 2019)
One way to improve curcumin's possibility in preventing lipid peroxidation is through modification of carbon linker, β-diketone group and aromatic rings. However, there remains a need to explore the role of carbon linker on the free radical scavenging mechanisms of curcumin. This study uses density functional theory to explore two descriptors of free radical scavenging mechanisms, which are bond dissociation enthalpy (BDE) and adiabatic ionization potential (AIP) of curcumin and its analogues. Five analogues with different amount of carbon atoms in the linker in the presence / absence of β-diketone group are chosen. Our result shows that decreasing the amount of carbon atom from 7 to 5 atoms in the linker decreases the BDE at β-diketone group of the curcumin analogue. Moreover, increasing the amount of carbon atoms in the linker decreases the AIP of the analogues.